2014
DOI: 10.1371/journal.pone.0110075
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Selection on CDH2 May Be Related to the Behavioral Features of the Belgian Malinois

Abstract: The Belgian Malinois (BM) is an excellent working dog that typically shows a circling behavior when placed in a confined space. Moreover, individuals showing moderate running in circles (one kind of obsessive compulsive behavior) in confined spaces typically show better work performance compared to those without the circling behavior or to those with a serious circling behavior (which can be defined as an obsessive compulsive disorder (OCD)). To determine whether the candidate gene CDH2, Cadherin 2, which is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…As a result, breeding of dogs and genetic lines that may be at enhanced risk for behavioral pathology continues without the benefit of genetic and behavioral counseling. While dogs with behavioral conditions are excellent natural animal models for human psychiatric illnesses (Overall, 2000;Overall et al, 2001;Overall and Dunham, 2002;Dodman et al, 2010Dodman et al, , 2016Ogata et al, 2013;Cao et al, 2014), breed and individual health is primary and is improved by establishing and participating in such studies (O'Neill et al, 2014;Overall et al, 2014;van Rooy et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, breeding of dogs and genetic lines that may be at enhanced risk for behavioral pathology continues without the benefit of genetic and behavioral counseling. While dogs with behavioral conditions are excellent natural animal models for human psychiatric illnesses (Overall, 2000;Overall et al, 2001;Overall and Dunham, 2002;Dodman et al, 2010Dodman et al, , 2016Ogata et al, 2013;Cao et al, 2014), breed and individual health is primary and is improved by establishing and participating in such studies (O'Neill et al, 2014;Overall et al, 2014;van Rooy et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that by selecting for some attribute, an extreme variant of some behavioral association was selected for and expression varied depending on the dog's environment (Tiira et al, 2012) or utility, resulting in a series of liability genes contributing to various behavioral expressions. Cao et al (2014) proposed the latter process for Belgian malinois, where circling and tail chasing is frequently seen in working dogs, resulting in balancing selection for a genomic block of the CDH2 gene. It is possible that a similar process has occurred for noise reactivity/phobias in any of these breeds, were one to select for some degree of heightened responsivity.…”
Section: Resultsmentioning
confidence: 99%
“…We also examined the previously reported CCD-associated genes, including neuronal cadherin (CDH2) [22,23,60], catenin alpha 2 (CTNNA2) [22], ataxin-1 (ATXN1) [22], and plasma glutamate carboxypeptidase (PGCP) [22] in our sample. We found that SNPs within these genes (22 SNPs in CDH2, 12 SNPs in CTNNA2 and 81 SNPs in PGCP) exhibited significant differences between cases and controls at nominal P value of 0.05 (Chi-square tests), and the probability of observing normal significant SNPs in three of four genes was zero in randomly-selected genes (Supplementary Methods online).…”
Section: Population Stratification and Differentiation Analysismentioning
confidence: 99%
“…However, high energy and activity is often associated with increased arousal. For example, Belgian Malinois bred as MWDs exhibit high levels of excitement often resulting in spinning behavior when kenneled, which has been reported to be higher in individuals with better work performance due to a stronger desire to work (42). Maejima et al (33) found that higher levels of anxiety were associated with a stronger desire for work and successful certification as a drug detection dog.…”
Section: Emotional Reactivitymentioning
confidence: 99%